Phenotypes Associated with Second Chromosome P Element Insertions in Drosophila melanogaster. Issue 8 (1st August 2016) - Kahsai, Lily; Millburn, Gillian H; Cook, Kevin R
Abstract: In Drosophila melanogaster, P element transposition has been a productive means of insertional mutagenesis. Thousands of genes have been tagged with natural and engineered P element constructs. Nevertheless, chromosomes carrying P element insertions tend to have high levels of background mutations from P elements inserting and excising during transposition. Consequently, the phenotypes seen when P element-bearing chromosomes are homozygous are often not attributable to the P insertions themselves. In this study, 178 strains in the Bloomington Drosophila Stock Center collection with P insertions on the second chromosome were complementation tested against molecularly defined chromosomal deletions and previously characterized single-gene mutations to determine if recessive lethality or sterility is associated with the P insertions rather than background mutations. This information should prove valuable to geneticists using these strains for experimental studies of gene function.